Live Birth Rate of Frozen-Thawed Single Blastocyst Transfer After 6 or 7 Days of Progesterone Administration in Hormone Replacement Therapy Cycles: A Propensity Score-Matched Cohort Study - Yang, Xinhong; Bu, Zhiqin; Hu, Linli (Frontiers in Endocrinology, 2021)
Background: Progesterone administration before transfer in hormone replacement treatment (HRT) is crucial to pregnancy outcomes in frozen-thawed blastocyst transfer (FET), but the optimal progesterone duration is inconsistent. The objective of this study was to investigate live birth rate (LBR) of different progesterone duration before blastocyst transfer in HRT-FET cycles. Method: In this retrospective cohort study, patients underwent first HRT-FET (including suppression HRT) from January 2016 to December 2019 were included. Logit-transformed propensity score matching (PSM) was performed to assess covariates. The primary outcome was live birth rate after 28 weeks’ gestation. Basing on different duration of progesterone before transfer, patients were classified into P6-protocol (blastocyst transfer performed on 6th day), or P7-protocol (blastocyst transfer performed on 7th day). Subgroup analyses were conducted as follows:age stratification (-35, 35-38, 38-), development days of blastocyst (D5 or D6), blastocyst quality (high-quality or poor-quality) , and endometrial preparation protocols (HRT or suppression HRT). Result: After case matching with propensity score methods, a total of 1,400 patients were included finally: 700 with P6-protocol and 700 with P7-protocol. Significantly higher live birth rate (38.43% versus 31.57%, respectively, P = 0.01) and clinical pregnant rate (50.43% versus 44.14%, respectively, P = 0.02) were observed in P6-protocol than those of P7-protocol. First-trimester abortion rates (18.13% versus 20.71%, P = 0.40) and ectopic pregnancy rates (2.27% versus 1.94% , P = 0.77) were similar between P6- and P7- groups . Preterm birth rate, low birth weight rate, newborn sex proportion, neonatal malformation rate were comparable between groups. Significantly higher LBRs were observed in patients with: age under 35, D5 blastocyst transfer, high-quality blastocyst transfer, undergoing HRT cycles combined P6-protocol. Conclusion: frozen-thawed blastocyst transfer on the 6th day of progesterone administration in first HRT cycle is related to higher live birth rate compared with transfer on the 7th day, especially among patients aged under 35, D5 blastocyst and/or high-quality blastocyst transfer.